The Effect Of Organizational Culture, Environmental Work, Leadership Style On The Job Satisfaction And Its Impact On The Performance Of Teaching In State Community Academy Bojonegoro (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2017)
Tri Dharma college task, namely implements education and teaching, research and community service. Some of the factors that can affect the performance of the lecturer are organizational culture, work environment, leadership style, and job satisfaction. For this study aims to assess the effect of organizational culture, work environment, leadership style on job satisfaction lecturers as well as to analyze the influence of organizational culture, work environment, leadership style to the performance of lecturers. This study took 64 samples through census methods, and data collected through questionnaires in the form of Likert scale research.  Results of analysis proving the hypothesis indicated that organizational culture, work environment, leadership style positive impact significant job satisfaction lecturer Bojonegoro State Community College. As well as organizational culture, work environment, leadership style, job satisfaction and positive effect significant the performance of lecturers Bojonegoro State Community College. Suggested to the management community college that faculty performance can be optimized, provide incentives for lecturers in order to work in the world of education through awards, strive to the increase salaries, keeping in touch, comfort, creation of competition, healthy  performance appraisal is fair, providing an opportunity to follow the scientific activities at a cost from the academy. Encourage to continue their education to a higher level. Motivate to do research, and community service to the relevant fields at the expense of the institution/college or grants.